England - Olson, Kay Melchisedech (Mankato, Minn. : Blue Earth Books, 2003)
Presents an introduction to England, discussing city and country life, seasons, families, laws, rules, customs, and pets, and including the English legend of "Robin Hood," and a list of places to visit.
Welcome to England -- An English legend -- City and country life -- Seasons in England -- Family life in England -- Laws, rules, and customs -- Pets in England -- Sites to see in England.
Includes bibliographical references (p. 30) and index.
Horn Book
Library Media Connection
5.7
3-6.
3-6
Keywords: England -- Juvenile literature; England; England